2014
DOI: 10.3389/fendo.2014.00007
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogs Therapy in Gastroenteropancreatic Neuroendocrine Tumors: Current Aspects and New Perspectives

Abstract: Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) are rare tumors that present many clinical features secreting peptides and neuroamines that cause distinct clinical syndromes such as carcinoid syndrome. However most of them are clinically silent until late presentation with mass effects. Surgical resection is the first line treatment for a patient with a GEP-NET while in metastatic disease multiple therapeutic approaches are possible. GEP-NETs are able to express somatostatin receptors (SSTRs) bounded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 103 publications
0
51
1
1
Order By: Relevance
“…This tumor cell-specific ligand-receptor approach could address currently unmet needs (38)(39)(40) in patients with unresectable, inoperable, or metastatic pancreatic NETs. Indeed, we have shown that Oct-AAVP-TNF reduced tumor size, metabolic activity, and hormone secretion, and also increased survival in the Men1 transgenic mouse model, which faithfully recapitulates human disease with respect to both progression and response to therapy (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…This tumor cell-specific ligand-receptor approach could address currently unmet needs (38)(39)(40) in patients with unresectable, inoperable, or metastatic pancreatic NETs. Indeed, we have shown that Oct-AAVP-TNF reduced tumor size, metabolic activity, and hormone secretion, and also increased survival in the Men1 transgenic mouse model, which faithfully recapitulates human disease with respect to both progression and response to therapy (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…No difference between imaging modalities ( 99m Tc EDDA/HYNIC-TOC vs. 18 F-FDG PET/CT or MRI) was noted. In group of NEC distant metastasis were found in 60% of the patients (3/5).…”
Section: Resultsmentioning
confidence: 88%
“…Patients using SSA showed symptomatic and biochemical improvement. SSA anti-tumor effects are still under investigation, they have direct impact on proliferative signaling pathways, on activation of apoptosis, on angiogenesis and on tumor stabilization [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…The expression of five subtypes of G-protein-coupled transmembrane somatostatin receptors (SSTRs) is very characteristic feature for NETs (54). Octreotide and lanreotide are somatostatin analogs proved to be useful in alleviation of of flushing and diarrhea which are associated with NETs secretion (55,56). The antitumor effect of somatostatin analogs has been established in many clinical trials (57)(58)(59).…”
Section: Neuropeptides and Cancermentioning
confidence: 99%